(untitled) - Andres M. Villa; Nelida S. Garretto; Tomoko Arakaki; Luciana Melamud; Sergio A. Rodríguez Quiroga; Luz Abaroa (Arquivos de Neuro-Psiquiatria)
Tonic spasms have been most commonly associated with multiple sclerosis. To date, few reports of series of patients with neuromyelitis optica and tonic spasms have been published.Methods:We analyzed the characteristics and frequency of tonic spasms in 19 subjects with neuromyelitis optica. Data was collected using a semi-structured questionnaire for tonic spasms, by both retrospectively reviewing medical records and performing clinical assessment.Results:All patients except one developed this symptom. The main triggering factors were sudden movements and emotional factors. Spasms were commonly associated to sensory disturbances and worsened during the acute phases of the disease. Carbamazepine was most commonly used to treat the symptom and patients showed good response to the drug.Conclusions:Tonic spasms are a common clinical manifestation in patients with neuromyelitis optica. Espasmos tônicos têm sido mais frequentemente associados com esclerose múltipla. Foram publicados até agora poucos relatos de série de pacientes com neuromielite óptica e espasmos tônicos.Métodos:Foram analisadas as características e a frequência de espasmos tônicos em 19 indivíduos com neuromielite óptica. Os dados foram coletados por meio de um questionário semiestruturado para espasmos tônicos, mediante a avaliação retrospectiva dos prontuários e a análise dos dados clínicosResultados:Todos os pacientes com neuromielite óptica exceto um apresentaram espasmos tônicos. Os principais fatores desencadeantes foram movimentos bruscos e fatores emocionais. Espasmos foram frequentemente associados a perturbações sensoriais e se agravaram durante a fase aguda da doença. A carbamazepina foi utilizada frequentemente para tratar os sintomas, com boa resposta.Conclusões:Os espasmos tônicos são manifestações clínicas frequentes em pacientes com neuromielite óptica.